Synergistic Sintering of Lignite Fly Ash and Steelmaking Residues towards Sustainable Compacted Ceramics - V. G. Karayannis; A. K. Moutsatsou; A. N. Baklavaridis; E. L. Katsika; A. E. Domopoulou (Advances in Materials Science and Engineering)
The development of value-added ceramic materials deriving only from industrial by-products is particularly interesting from technological, economic, and environmental point of views. In this work, the synergistic sintering of ternary and binary mixtures of fly ash, steelmaking electric arc furnace dust, and ladle furnace slag for the synthesis of compacted ceramics is reported. The sintered specimens’ microstructure and mineralogical composition were characterized by SEM-EDS and XRD, respectively. Moreover, the shrinkage, apparent density, water absorption, and Vickers microhardness (HV) were investigated at different sintering temperatures and raw material compositions. The characterization of the sintered compacts revealed the successful consolidation of the ceramic microstructures. According to the experimental findings, the ceramics obtained from fly ash/steel dust mixtures exhibited enhanced properties compared to the other mixtures tested. Moreover, the processing temperature affected the final properties of the produced ceramics. Specifically, a 407% HV increase for EAFD and a 2221% increase for the FA-EAFD mixture were recorded, by increasing the sintering temperature from 1050 to 1150°C. Likewise, a 972% shrinkage increase for EAFD and a 577% shrinkage increase for the FA-EAFD mixture were recorded, by increasing the sintering temperature from 1050 to 1150°C. The research results aim at shedding more light on the development of sustainable sintered ceramics from secondary industrial resources towards circular economy.